PODEJŚCIE STUDENTÓW FILOLOGII ANGIELSKIEJ DO REFLEKSJI W NAUCE WYMOWY - Baran-Łucarz, Małgorzata (Neofilolog, 2019)
This paper aims to report attitudes of extramural students of the Department of English Studies, University of Wrocław, towards reflection which was introduced into a course of phonetics and into individual practice of pronunciation at home. The article opens with a brief presentation of the concept of reflection, a discussion of its importance in teaching foreign languages (FLs) and an overview of studies on the use of reflection in FL pronunciation teaching. The research design and the techniques used to develop reflection in the students in this study are then described. From the perspective of many learners involved in this research introducing reflection into pronunciation learning had several positive effects: it helped learners set goals and made them aware of effective learning strategies. It also aided them in self-evaluation, in understanding the emotions accompanying the learning of FL pronunciation, and in finding ways of dealing with these. However, it was found that many students were reluctant to have reflection introduced into the learning process. This was mainly due to lack of time and to students’ belief that reflection does not bring any positive results. Finally, the author suggests that the ability to reflect on one’s learning is difficult and dependent on individual predisposition, and that it requires special training.